Water Resources Management Models for Policy Assessment - Garrote, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a compilation of original research articles that apply a variety of techniques to identify and evaluate water resource management policies. These papers cover a wide range of topics and methodologies applied across the world, from a local to a continental scope. They illustrate open challenges in water resource management, such as the quantitative assessment of policy impacts, trade-off analyses, understanding the water-energy-food-environment nexus, collaborative model development, stakeholder engagement, formalizing social interactions, or improving the theoretical understanding of complex adaptive systems. Therefore, this book is a representation of research areas that have emerged from the origins of water resource systems analysis, seeking to improve the way in which water policy is formulated and implemented.